Impact of entrepreneurial orientation on small, medium enterprises performance in Lesotho - Phoofolo, Mamonono Sebueng Adel (My University, 2018)
Global business environment recently have a complexity in conducting business transactions. Entrepreneurial Orientation (EO) can be considered a significant factor for ensuring the success of a business, however firms are forced to be involved in seeking out new opportunities. Businesses need to identify opportunities in order to establish capabilities and potentials which will enable them to be innovative, proactive and have propensity to take risks so that they can enhance performance or retain competitive advantage. Apart from that, external business environment within their operation should be considered as an ongoing process to SMEs in order to respond to environmental challenges rapidly and competently. This study explored the impact of Entrepreneurial Orientation which is presented by three dimensions namely; innovativeness, proactiveness, and risk taking and performance. Cross sectional survey was employed on 118 SMEs through convenience sampling to establish the relationship between EO and performance taking into account environmental contingencies. Data was collected by a valid and reliable questionnaire and analysed. The study found that, in Lesotho context two factors; proactiveness and innovativeness of the SMEs have influence on EO-performance relationship, while risk taking did not have a major effect in this relationship. The other finding indicated that external environment influences the relationship between EO and a firm’s performance. The findings of this study is expected to be beneficial to entrepreneurs, SMEs owners, future researches and policy makers in the Government by assisting to identify the gaps to enhance and encourage EO.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management. March, 2018
Keywords: Business enterprises--Lesotho; Small business--Lesotho